Enhancing Plantation Productivity: A Screen-house Investigation into the Impact of Indaziflam on Amaranthus, Maize, Melon, and Tomato in Intercropping Systems - Isesele John Imomoh; Olatunde Philip Ayodele; Celestine Ebehiremhe Ikuenobe (Tunisian Journal of Plant Protection)
Imomoh, I.J., Ayodele, O.P., and Ikuenobe, C.E. 2024. Enhancing plantation productivity: A screen-house investigation into the impact of indaziflam on amaranthus,maize, melon, and tomato in intercropping systems. Tunisian Journal of Plant Protection 19 (2): 87-100.